A catalogue of the nematode slide collection from the late W.L. Nicholas held at National Research Collections Australia, CSIRO - Khudhir, Manda; Hodda, Mike; Nicholas, Evelyn; Campbell, Jennifer; Nicholas, Warwick L. (Zootaxa, 2023)
A catalogue is presented of the nematode slide collection of W.L. Nicholas, which is deposited in the National Research Collections Australia at CSIRO. This is the most extensive slide collection of free-living marine and estuarine nematodes from Australia to date, and consists of 553 putative species, collected across a wide range of Australia’s eastern and northern regions over the course of nearly 40 years. The collection contains mostly marine and estuarine free-living nematodes collected on coarse substrate in littoral habitats. The most abundant genera were Desmodora, Theristus, and Onyx. Most taxa were found rarely, being recorded only once, and repeated sampling at several sandy beach sites revealed only a small proportion of the fauna on more than one occasion. A significant proportion of the taxa were also found to be widespread, occurring on more than one occasion at more than one location, with Theristus sp., Onyx sp., and Viscosia sp. occurring in the greatest number of localities. The catalogue adds an additional 90 species and 160 genera to the documented fauna of Australian free-living nematodes verifiable by specimens in permanent collections. It thus provides a better framework for studying nematode biodiversity and biogeography in the region.